2007
DOI: 10.1111/j.1574-695x.2007.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in vaccine development againstHelicobacter pylori

Abstract: Based on the very high prevalence of diseases caused by Helicobacter pylori, particularly in the developing world, and the rapid emergence of antibiotic resistance among clinical isolates, there is a strong rationale for an effective vaccine against H. pylori. In this review we describe recent promising candidate vaccines and prophylactic or therapeutic immunization strategies for use against H. pylori, as well as studies to identify immune responses that are related to protection in experimental animals. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 81 publications
2
33
0
Order By: Relevance
“…In the past decade, several vaccine candidates against H. pylori have been evaluated in animal models (2). We and others have shown that, besides specific H. pylori antigens, an effective adjuvant is needed to induce protection against H. pylori infection after mucosal immunization (2,3).…”
Section: A Pproximately Half Of the World's Population Is Infected Withmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, several vaccine candidates against H. pylori have been evaluated in animal models (2). We and others have shown that, besides specific H. pylori antigens, an effective adjuvant is needed to induce protection against H. pylori infection after mucosal immunization (2,3).…”
Section: A Pproximately Half Of the World's Population Is Infected Withmentioning
confidence: 99%
“…We and others have shown that, besides specific H. pylori antigens, an effective adjuvant is needed to induce protection against H. pylori infection after mucosal immunization (2,3). Thus, immunization with whole-cell or lysate preparations of H. pylori together with adjuvants such as cholera toxin (CT) or heat-labile toxin (LT) and in some cases also mutant forms of the toxins confers protection against H. pylori infection (2,4). CT, most often used in the preclinical evaluation of mucosal candidate vaccines, promotes strong T cell as well as B cell responses to vaccine components and is a golden standard for testing alternative mucosal adjuvants.…”
Section: A Pproximately Half Of the World's Population Is Infected Withmentioning
confidence: 99%
“…The explanation for these differences may be related to the fact that the C57BL/6 mice are prone to developing a Th1 polarized T cell response and BALB/c mice a Th2 type of response. Infection of C57BL/6 mice with H. pylori strain SS1 is by far the most robust and reproducible of all mouse models and has been extensively used to study vaccine-induced immune responses and protection against H. pylori infection (reviewed in Svennerholm and Lundgren, 2007;Muller and Solnick, 2011;Zawahir et al, 2013).…”
Section: Animal Models Of H Pylori-induced Gastritismentioning
confidence: 99%
“…The development of resistance would presumably be a less likely shortcoming for an effective vaccine. In murine models, immune responses induced to bacterial urease [50] protect against oral challenge with Helicobacter, suggesting that a prophylactic vaccine against Helicobacter might be possible [51]. However, clinical trials with single antigens have thus far been disappointing, which has stimulated efforts to consider vaccines composed of several antigens.…”
Section: Helicobacter Pylorimentioning
confidence: 99%